The Development Of Bedil Island Marine Tourism Inspired By Raja Ampat As A Tourist Attraction In Banyuwangi - Pratiwi, Yosi Mulyana; Ningrum, Nadiya Lifa (UNIVERSITAS PAKUAN, 2025)
Banyuwangi is the largest region in East Java and is home to one of the underdeveloped marine tourism assets—Bedil Island, a small island with tremendous potential due to its beautiful beaches, crystal-clear waters, and pristine marine biodiversity, resembling that of Raja Ampat. Considering the success of Raja Ampat's tourism branding and management, it is important to explore the development of Bedil Island without losing its local uniqueness. This study aims to examine the potential and development strategies for Bedil Island's marine tourism, inspired by the Raja Ampat model, as a new attraction for both domestic and international tourists. This research employs a descriptive qualitative method with a case study approach. Data sources include both primary and secondary data. The data analysis techniques used are data reduction, data display, and conclusion drawing and verification. To ensure data validity, triangulation of sources and methods was applied. The findings reveal that Bedil Island holds great potential to be developed as a leading tourism destination in Banyuwangi. Its main attractions include a cluster of small islands, clear turquoise-blue seawater, and distinctive natural beauty. Accessibility to the location is relatively feasible: visitors can travel approximately two hours by land from Banyuwangi city center, followed by a boat trip to the Bedil Island cluster. Key attractions and unique features of Bedil Island include: snorkeling and diving, sailing around the island cluster, trekking to Kemuning peak, marine educational tourism, and local seafood culinary experiences such as grilled fish and other seafood dishes.